2000
DOI: 10.1161/01.atv.20.5.1189
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Tyrosine Phosphatases in the Vessel Wall

Abstract: Abstract-Many protein-tyrosine phosphatases (PTPases) have now been identified, but little is known about PTPase expression and regulation in vascular tissue and in vascular disease. Polymerase chain reaction (PCR) amplification and cDNA fingerprinting of PTPase catalytic domains, combined with random sequencing of PCR product libraries, identified 18 (8 receptor-like and 10 cytosolic) PTPases in the rat carotid artery and revealed differential expression of 5 of these PTPases during neointima formation after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…27,28 Therefore, we assessed whether PTP1B was indeed present in the small peripheral arteries used in our functional study. PCR experiments showed that small mesenteric arteries express PTP1B mRNA, and the presence of the enzyme was confirmed by Western blotting.…”
Section: Circulation December 5 2006mentioning
confidence: 99%
“…27,28 Therefore, we assessed whether PTP1B was indeed present in the small peripheral arteries used in our functional study. PCR experiments showed that small mesenteric arteries express PTP1B mRNA, and the presence of the enzyme was confirmed by Western blotting.…”
Section: Circulation December 5 2006mentioning
confidence: 99%
“…3. The balloon injury method was equally successful in denudation but caused significant damage to the media and in particular to the internal elastic lamina (5,6,16,19,22,24,25). Finally, the denudation was confirmed by the lack of contraction in the presence of norepinephrine (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The PTPs constitute a family of more than 75 enzymes, with as many as 18 identified in rat vascular smooth muscle (Schaapveld et al, 1997;Wright et al, 2000). The conventional PTPs are classified into two broad groups, the receptor-like and the cytoplasmic or nonmembrane groups (Wright et al, 2000;Tonks and Neel, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The PTPs constitute a family of more than 75 enzymes, with as many as 18 identified in rat vascular smooth muscle (Schaapveld et al, 1997;Wright et al, 2000). The conventional PTPs are classified into two broad groups, the receptor-like and the cytoplasmic or nonmembrane groups (Wright et al, 2000;Tonks and Neel, 2001). The receptor-like PTPs exhibit transmembrane components that are directly activated by integrins and similar intrinsic molecules, whereas the cytoplasmic PTPs are activated by signaling cascades that can involve classic receptor occupancy and G protein intermediates.…”
Section: Discussionmentioning
confidence: 99%